Incidental ventral gallbladder herniation in an asymptomatic patient: A case report - Rasha Arekat; Yazan Dibas (Radiology Case Reports, 2025)
Gallbladder herniation is a rare clinical finding that can present with a wide spectrum of symptoms, ranging from asymptomatic incidental discoveries to acute abdominal emergencies. We present the case of a middle-aged individual with a background of 2 previous laparotomies, in whom gallbladder herniation was incidentally detected via computed tomography (CT) conducted for unrelated reasons. The patient was completely asymptomatic, with no evidence of inflammation, obstruction, or biliary disease. Given the lack of clinical complications, a conservative, non-operative management approach was chosen. This case highlights the importance of identifying gallbladder herniation in patients with a history of abdominal surgeries as well as the critical function of imaging in its identification. While the majority of instances recorded in the literature involve symptomatic patients requiring surgical intervention, our study contributes to the small number of asymptomatic cases managed conservatively, emphasizing the variability in clinical presentation and the importance of individualized care.